Disaster Management of Pandemic COVID-19 toward Tourism of Bintan Regency by NVivo Analysis - Mahadiansar, Mahadiansar; Pratiwi, Mirza Ayunda; Putri, Rizqi Apriani; Valentina, Annissa (Journal of Governance and Public Policy, 2023)
Bintan Regency has a strategic location close to Singapore (it only takes 60 minutes by ferryboat). Therefore, tourism is one of the primary sectors contributing to the highest local government revenue of the Bintan Regency. During the COVID-19 pandemic, all the entrances from abroad were closed. Then it finally decreased to 94% of the local government revenue. The Ministry of Tourism and Creative Economy has recommended the "Travel Bubble" Policy to welcome the new average era without ignoring health protocols. The travel bubble is also one of the disaster management efforts in the tourism sector. Bintan Regency is one of the pilot projects to implement the travel bubble in Indonesia. This study aims to analyze the possibilities of implementing the Travel Bubble. The research also described the policy, the government's role, and matters relating to strategic policies on the performance of the travel bubble. The findings of this study resulted from qualitative data with the NVIVO 12 software tool. The results showed a matrix coding query about the predictions of the type of tourist attraction that will contribute highly to tourist interest. Then, the results recommend an effective collaboration between the central and local governments. However, the local governments must take a role dominantly. This study also explains the attempt to manage tourism disasters. Finally, the readers can use this study to analyze various strategic policies revitalizing the tourism economy.